Point-of-Care Ultrasound: New Concepts and Future Trends - Yaoting Wang, MD, Huihui Chai, MD, Ruizhong Ye, MD, Jingzhi Li, MD, PhD, Ji-Bin Liu, MD, Chen Lin, Chengzhong Peng, MD (Editorial Office of Advanced Ultrasound in Diagnosis and Therapy, 2021)
Ultrasound (US) technology, with major advances and new developments, has become an essential and first-line imaging modality for clinical diagnosis and interventional treatment. US imaging has evolved from one-dimensional, two-dimensional to three-dimensional display, and from static to real-time imaging, as well as from structural to functional imaging. Based on its portability and advanced digital imaging technique, US was first adopted by emergency medicine in the 1980s and gradually gained popularity among other specialists for clinical diagnosis and interventional treatment. Point-of-Care Ultrasound (POCUS) was then proposed as a new concept and developed for new uses, which greatly extended clinical US applications. Nowadays, artificial intelligence (AI), cloud computing, 5G network, robotics, and remote technologies are starting to be integrated into US equipment. US systems have gradually evolved to an intelligent terminal platform with powerful imaging and communication tools. In addition, specialized US machines tend to be more suitable and important to meet increasing demands and requirements by various clinical specialties and departments. In this article, we review current US technology and POCUS as new concepts and its future trends, as well as related technological developments and clinical applications.